Molecular analysis of the F4 progenies obtained through pollen selection for heat tolerance in maize (Zea mays) - SURESH H ANTRE; ASHUTOSH SINGH; R L RAVIKUMAR (The Indian Journal of Agricultural Sciences, 2023)
In the present study, three sets of F4 progeny lines developed through different cycles of pollen selection for heat tolerance were studied for the genetic differences using 16 SSR markers during 2017–20 at Department of Plant Biotechnology, University of Agricultural Sciences, Gandhi Krishi Vignana Kendra, Bengaluru, Karnataka. Three groups of F4 progenies used for the study are GGG (pollen selection for heat tolerance in F1, F2 and F3 generation); GCG (pollen selection for heat tolerance only in F1 and F3 generation); CCC (no pollen selection for heat tolerance in F1, F2 and F3 generation). Five randomly selected F4 lines of the cross of heat stress susceptible BTM4 and heat tolerant BTM6 represented each group. The three groups differed significantly for the number of male parent alleles as evidenced by SSR markers. The F4 (GGG) progenies had significantly more number of male parent type alleles compared to F4 (GCG) and F4 (CCC) lines. The F4 (CCC) lines recorded more number of female alleles compared to other F4 (GGG and GCG) lines. The effectiveness of pollen selection for heat tolerance towards increasing the frequency of male parent alleles and their transmission to the succeeding progenies has been demonstrated in the present study.